Tourism policy reform: the case of Padang City, Indonesia - Indrianto, Hendri Agung (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
The purpose of this study is to find out why Padang, being an attractive tourism destination, has failed to become a popular tourist destination in Indonesia. This descriptive and qualitative study obtains its data from official government documents, books, academic journals, statistical data, interviews and official information from credible sources. Padang's tourism policy development and implementation are also examined using the New Public Management theories with an analytical framework which assumes that a well developed, coordinated and implemented tourism policy will result in a profitable tourism industry. The study finds that poor development, coordination and implementation of a country's tourism policies and planning will have a significant negative impact on the success of the tourism industry in the region.